ChemInform Abstract: Hydrothermal Synthesis and Magnetic Characterization of the Quaternary Oxide CoMo2Sb2O10. Issue 52 (6th December 2016) - Ali, Sk Imran; Kremer, Reinhard K.; Johnsson, Mats
Abstract: Green single crystals of CoMo2 Sb2 O10 are prepared by hydrothermal reaction of a 1:2:1 molar mixture of CoF2, MoO3, and Sb2 O3 in diluted aq.